Just preparation for war and AI-enabled weapons - Regan, Mitt; Davidovic, Jovana (Frontiers in Big Data, 2023)
This paper maintains that the just war tradition provides a useful framework for analyzing ethical issues related to the development of weapons that incorporate artificial intelligence (AI), or “AI-enabled weapons.” While development of any weapon carries the risk of violations of jus ad bellum and jus in bello, AI-enabled weapons can pose distinctive risks of these violations. The article argues that developing AI-enabled weapons in accordance with jus ante bellum principles of just preparation for war can help minimize the risk of these violations. These principles impose two obligations. The first is that before deploying an AI-enabled weapon a state must rigorously test its safety and reliability, and conduct review of its ability to comply with international law. Second, a state must develop AI-enabled weapons in ways that minimize the likelihood that a security dilemma will arise, in which other states feel threatened by this development and hasten to deploy such weapons without sufficient testing and review. Ethical development of weapons that incorporate AI therefore requires that a state focus not only on its own activity, but on how that activity is perceived by other states.